Analyzing the Disruptive Effects of Irregular Power Supply on Student Academic Performance and Administrative Oversight in Technical Education - Kumar, Teki Yaswanth; Babu, Kishore (Journal of Research in Vocational Education, 2025)
This study explores the impact of untimely power cuts on the pedagogical supervision and practical learning of students in technical schools in the Kikula commune, focusing on the general electricity option. Using a sample of 120 participants, including students and workshop teachers, the research reveals that frequent power outages hinder the effective implementation of practical sessions, thereby obstructing students' ability to acquire essential technical skills. Teachers face challenges in achieving curriculum objectives, while students struggle with motivation and comprehension of theoretical concepts. The findings highlight the need for reliable electricity in technical workshops and propose the development of alternate power sources and improved infrastructure. Recommendations include targeted measures for students, teachers, authorities, and scientists to ensure effective training and skill acquisition in technical education.